Minimally Invasive Harvesting of Triple-Fold Superficial Layer Quadriceps Autograft for Knee Ligament Reconstruction - Napatpong Thamrongskulsiri, M.D.; Danaithep Limskul, M.D.; Thanathep Tanpowpong, M.D.; Somsak Kuptniratsaikul, M.D.; Thun Itthipanichpong, M.D. (Arthroscopy Techniques, 2023)
Graft selection plays a critical role in anterior cruciate ligament reconstruction. Autograft options, including hamstrings, bone–patellar tendon–bone, and quadriceps, offer distinct advantages and disadvantages. Soft tissue quadriceps tendon autografts are increasingly favored due to their strength, size compatibility, and potential for enhanced graft healing. This technique offers minimal skin incision, a longer graft, and reduced morbidity, as it specifically targets the superficial band of the quadriceps tendon.